Amazing tales from the world of ravens - Sarosiek, Anna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Book review: Bernd Heinrich, Umysł kruka. Badania i przygody w świecie wilczych ptaków, tł. Michał Szczubiałka, Wydawnictwo Czarne, Wołowiec, 2018, ss. 504.
Keywords: animal intelligence; mind; cognitive science; raven